2017
DOI: 10.1016/j.nbd.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous triple therapy for the treatment of status epilepticus

Abstract: Early maladaptive internalization of synaptic GABAA receptors (GABAA R) and externalization of NMDA receptors (NMDAR) may explain the time-dependent loss of potency of standard anti-epileptic drugs (AED) in refractory status epilepticus (SE). We hypothesized that correcting the effects of changes in GABAAR and NMDAR would terminate SE, even when treatment is delayed 40 minutes. SE was induced in adult Sprague-Dawley rats with a high dose of lithium and pilocarpine. The GABAAR agonist midazolam, the NMDAR antag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 34 publications
1
60
0
Order By: Relevance
“…A recent study demonstrated that perampanel terminated status epilepticus in a pilocarpine model of status epilepticus, but amantadine, an NMDA receptor antagonist, did not [163]. Similarly, the NMDA antagonist ketamine did not demonstrate a stable effect in animal models of status epilepticus when administered as monotherapy, but showed synergistic efficacy when administered in combination therapy with other drugs [165][166][167][168]. As such, AMPA antagonists appear to have an advantage over NMDA antagonists in the termination of self-sustained synchronized activity.…”
Section: Synchronized Activitymentioning
confidence: 99%
“…A recent study demonstrated that perampanel terminated status epilepticus in a pilocarpine model of status epilepticus, but amantadine, an NMDA receptor antagonist, did not [163]. Similarly, the NMDA antagonist ketamine did not demonstrate a stable effect in animal models of status epilepticus when administered as monotherapy, but showed synergistic efficacy when administered in combination therapy with other drugs [165][166][167][168]. As such, AMPA antagonists appear to have an advantage over NMDA antagonists in the termination of self-sustained synchronized activity.…”
Section: Synchronized Activitymentioning
confidence: 99%
“…When treatment is delivered late, there may not be enough GABA A Rs left in synapses to fully restore inhibition, and an additional AED which enhances inhibition at a nonbenzodiazepine site provides additional benefit [15]. The choice of the best AED for that purpose would require too much space for this brief review.…”
Section: Choice Of Drugsmentioning
confidence: 99%
“…The results support the receptor trafficking hypothesis. Methods have been published [14,15] and will not be described in this brief review.…”
mentioning
confidence: 99%
“…In cholinergic stimulation models of SE, NMDA receptor antagonists alone are ineffective in terminating benzodiazepine‐refractory SE. However, when these drugs are combined with benzodiazepines, they work synergistically to end seizures …”
Section: Role Of Nmda Receptors In Sementioning
confidence: 99%
“…However, when these drugs are combined with benzodiazepines, they work synergistically to end seizures. [15][16][17] SE results in neuronal injury and death. Both necrotic and programmed cell death are reported to occur as a result of SE.…”
Section: Role Of Nmda Receptors In Sementioning
confidence: 99%